"Pro-summer power! how to create wealth by buying smarter, not cheaper" - "Quain, Bill" (Bhopal, 2007)
This book describes of how today's consumer economy works and points out the marketing tricks that stores uses to make consumers buy on an impulse. According to the author Dr. Bill Quain, who is a marketing expert, average people can produce above-average wealth through the power of prosuming. This book is a must read for people who would love to create 'income' instead of 'out-go' when they shop.
Keywords: Wealth